Ibrutinib for the treatment of chronic graft‐vs‐host disease in pediatric hematopoietic stem cell transplant patients: A single‐center experience. (23rd March 2020) - Teusink‐Cross, Ashley; Davies, Stella M.; Grimley, Michael S.; Chandra, Sharat; Flannery, Amanda; Dandoy, Christopher E.; Nelson, Adam S.; Marsh, Rebecca A.; Jacoby, Brandon; Lane, Adam; Khandelwal, Pooja
Abstract: cGVHD is a significant cause of morbidity and mortality after transplant. Ibrutinib has been studied as treatment for cGVHD in the adult population. Pediatric dosing and safety of ibrutinib are unknown. We conducted a retrospective review on the use of ibrutinib in 22 children with cGVHD at Cincinnati Children's Hospital Medical Center. All patients received a dose of 250 mg/m 2 orally, once daily. Responses were measured at 6 months after drug initiation using the 2014 NIH consensus panel response criteria. Twenty‐two patients of median age 13.5 years received ibrutinib. cGVHD grades were severe (n = 15), moderate (n = 6), and mild (n = 1). Eight patients stopped ibrutinib prior to 3 months due to adverse events or death and could not be evaluated for 6‐month response. Of the 14 evaluable patients, 12 achieved a partial response at 6 months and two patients had progressive disease. Seven evaluable patients with lung involvement had stable lung function at 6 months. One patient had EBV reactivation, and one patient developed pneumococcal sepsis despite appropriate prophylaxis while on ibrutinib therapy. No fungal infections occurred while on ibrutinib. Adverse events leading to discontinuation included recurrent fevers without a source, extensive bruising, oral bleeding, gastrointestinal distress, lower GI bleeding, dizziness, elevated transaminases, and pneumococcal sepsis. Ibrutinib administration of 250 mg/m 2 oral daily shows promising responses in pediatric cGVHD. Pediatric‐focused pharmacokinetic‐directed studies are needed to establish optimal dosing and define efficacy in children.